The probe attack on the Bennett-Brassard 1984 protocol in the presences of noisy amplitude damping channel - Abdel-Hameed, Hossam Farouk; Zidan, Nour A.; Wahiddin, Mohamed Ridza (Springer US, 2017)
In this contribution, we investigate the effect of the generalized amplitude damping as Eve's strategy to cause an error on the received signal during generating a quantum key distribution between Alice and Bob using Bennett-Brassard 1984 (BB84) protocol. For small values of the channel strength and larger values of the decay parameter, the entanglement decays gradually. The phenomena of the sudden changes of entanglement are observed for smaller and larger values of the willing initial error. These changes of entanglement decay gradually when Alice prepares her qubit in horizontal-vertical basis. While the sudden changes are depicted if the initial state is prepared in the diagonal-anti-diagonal basis. Bob will get his measurement with an error, where the probability of this error depends on the initial polarized angle, the initial desired error and the channel parameters.